Evolución de las regalías y su incidencia en el desarrollo territorial del departamento de Casanare en el periodo 2010 – 2018 (2021)
In Colombia, different activities related to the hydrocarbon sector are managed to improve and help the economic growth of the country, among which is the extraction of oil carried out by large oil companies that generate surpluses, well called royalties, which are a percentage between 8% and 25% that is paid to the Colombian State to be destined to the solution of the population's needs, such as education, health, and drinking water and sewerage. To make use and adequate distribution of the resources generated by royalties, the General System of Royalties is created, which is based on the principle of decentralization and autonomy of the territorial entities.